Harrison's nephrology and acid-base disorders - Harrison, Tinsley Randolph, 1900-1978.; Jameson, J. Larry; Loscalzo, Joseph (New York : McGraw-Hill Education/Medical, 2013)
Featuring a compilation of chapters related to kidney function that appear in Harrison's Principles of Internal Medicine, Eighteenth Edition, this concise, full-color clinical companion delivers the latest knowledge in the field backed by the scientific rigor and authority that have defined Harrison's. You will find content from renowned editors and contributors in a carry-anywhere presentation that is ideal for the classroom, clinic, ward, or exam/certification preparation. Complete coverage of a broad spectrum of topics, including acid-base and electrolyte disorders, vascular injury to the kidney, and specific diseases of the kidney. Integration of pathophysiology with clinical management. 41 high-yield questions and answers drawn from Harrison's Principles of Internal Medicine Self-Assessment and Board Review, 18 edition. Content updates and new developments since the publication of Harrison's Principles of Internal Medicine, 18 edition, with 22 chapters written by physicians who are recognized experts in the field of nephrology and acid-base disorders. Helpful appendix of laboratory values of clinical importance
Cellular and molecular biology of the kidney / Alfred L. George Jr., Eric G. Neilson -- Adaptation of the kidney to renal injury / Raymond C. Harris, Eric G. Neilson -- Azotemia and urinary abnormalities / Julie Lin, Bradley M. Denker -- Atlas of urinary sediments and renal biopsies / Agnes B. Fogo, Eric G. Neilson -- Acidosis and alkalosis / Thomas D. Dubose Jr. -- Fluid and electrolyte disturbances / David B. Mount -- Hypercalcemia and hypocalcemia / Sundeep Khosla -- Hyperuricemia and gout / Christopher M. Burns ... [et al.] -- Nephrolithiasis / John R. Asplin, Fredric L. Coe, Murray J. Favus -- Acute kidney injury / Sushrut S. Waikar, Joseph V. Bonventre -- Chronic kidney disease / Joanne M. Bargman, Karl Skorecki -- Dialysis in the treatment of renal failure / Kathleen D. Liu, Glenn M. Chertow -- Transplantation in the treatment of renal failure / Anil Chandraker, Edgar L. Milford, Mohamed H. Sayegh -- Infections in kidney transplant recipients / Robert Finberg, Joyce Fingeroth -- Glomerular diseases / Julia B. Lewis, Eric G. Neilson -- Polycystic kidney disease and other inherited tubular disorders / David J. Salant, Craig E. Gordon -- Tubulointerstitial diseases of the kidney / Laurence H. Beck, David J. Salant -- Vascular injury to the kidney / Stephen C. Textor, Nelson Leung -- Hypertensive vascular disease / Theodore A. Kotchen -- Urinary tract infections, pyelonephritis, and prostatitis / Barbara W. Trautner, Kalpana Gupta -- Urinary tract obstruction / Julian L. Seifter -- Bladder and renal cell carcinomas / Howard I. Scher, Robert J. Motzer
Compilation of chapters related to kidney function from Harrison's principles of internal medicine. 18th edition, 2012
Includes bibliographical references and index
13
Keywords: Acid-base imbalances; Kidneys -- Diseases; Nephrology; Acid-base imbalances; Kidneys -- Diseases; Nephrology; Acid-Base Imbalance; Kidney Diseases; Kidney -- pathology